2012
DOI: 10.1186/1757-2215-5-26
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivities of androgen receptor, estrogen receptors, p450arom, p450c17 proteins in wild ground squirrels ovaries during the nonbreeding and breeding seasons

Abstract: The aim of this study was to elucidate the regulatory role of androgen in the follicular development of wild female ground squirrels. Immunohistochemical staining of FSHR, LHR, P450c17, P450arom, androgen receptor (AR), estrogen receptors (ERa and ERb) were executed in ovaries of female ground squirrels from both breeding and nonbreeding seasons. In addition, total ovarian proteins were extracted from the ovaries of squirrels from breeding and nonbreeding seasons, and Western blot analysis were performed in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…The present histological result was in agreement with previous data reported in this species, that the number of primary follicles had no significant difference between the breeding and nonbreeding seasons, whereas the number of secondary follicles, antral follicles, post-antral follicles and corpus luteum displayed a significantly decrease from the breeding season to the nonbreeding season [28,29]. It suggested that primary follicles were stopped from developing to the stage of secondary follicles, antral follicles, post-antral follicles during nonbreeding season in the wild ground squirrel ovary.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present histological result was in agreement with previous data reported in this species, that the number of primary follicles had no significant difference between the breeding and nonbreeding seasons, whereas the number of secondary follicles, antral follicles, post-antral follicles and corpus luteum displayed a significantly decrease from the breeding season to the nonbreeding season [28,29]. It suggested that primary follicles were stopped from developing to the stage of secondary follicles, antral follicles, post-antral follicles during nonbreeding season in the wild ground squirrel ovary.…”
Section: Discussionsupporting
confidence: 93%
“…The wild female ground squirrel exhibits estrus immediately after emergence from hibernation in spring, and has a gestation period of 28 days [28]. Whether fertilized or not, all females become sexually inactive as the relatively brief breeding season ends.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of HAS2, PTX3, PTGS2, BCL2 L11, PCK1 and GREM1 transcripts in human (McKenzie et al 2004;Zhang et al 2005;Cillo et al 2007;Assou et al 2008;Gebhardt et al 2011), HAS2, PTX3, PTGS2, CDX3 andGREM1 in cow (Assidi et al 2008) Ϫ4 and Has2, Ptgs2 and Alcam in mouse (Adriaenssens et al 2011) were correlated with good preimplantation development and pregnancy outcome. In contrast, the expression of other groups of genes was found to be higher in human (GPX3, CXCR4, Regarding Fshr and Lhr proteins, both receptors have been analysed mainly in the theca and GCs of growing follicles in mouse (Choi et al 2011), rat (Bukovsky et al 2003;Armenti et al 2008), squirrel (Li et al 2012), porcine and human (Bukovsky et al 2003) ovaries, but their expression in CCs of fully grown follicles has not yet been reported. To the best of our knowledge, the present study is the first to describe their pattern of expression in mouse CCs surrounding fully grown antral oocytes and, furthermore, to demonstrate their differential expression in CCs of developmentally competent or incompetent follicles.…”
Section: Discussionmentioning
confidence: 94%
“…Suppression of P450arom activity can reduce the E 2 concentration in FF [35, 36]. In a study on women with polycystic ovary syndrome (PCOS), the P450arom expression levels in granulosa cells were very low and undetectable, indicating that the process of conversion of androgens into estrogens was disturbed, affecting the development of the ovarian follicle [37]. …”
Section: Discussionmentioning
confidence: 99%